Gender Disparities in Cardiovascular Complications of Type 2 Diabetes: Are Females More Frequently in Risk ? - Zaidi, Kissa; Kulshrestha, Divya; Chouhan, Aakriti (Asian Journal of Biological and Life Sciences, 2025)
Cardiovascular Disease (CVD) continues to be a major cause of death and dejection for people with Type 2 Diabetes Mellitus (T2DM). However, an increasing amount of evidence suggests that there is a gender difference in the risk and rate of cardiovascular problem development among T2DM patients. Due to disparities in hormone levels, metabolic regulation, and the impact of traditional cardiovascular risk factors, women, especially postmenopausal women, may be more vulnerable to heart attack or stroke than men. Gazing into the clinical, behavioral, and biological factors that influence this variation, the present investigation investigates the relationship between gender and cardiovascular problems in type 2 diabetes. Understanding these gender-based differences is essential to improving treatment outcomes, preventative strategies, and clinical care of women with type 2 diabetes.
Keywords: Cardiovascular Disease (CVD); Evaluation of Cardiovascular Outcome Results; GLP-1; Sodium Glucose Co-Transporter-2 (SGLT2); LEADER (Liraglutide Effect and Action in Diabetes